I AM: A devotional study of the attributes of God - BRIAN A. RUSSEL (Scotland Christian Focus Publications and Grace Publication Trust, 2019)
To have a clearer vision of God should be the Christian$1 (Bs supreme calling, because when we know Him we reflect Him. To love and serve the Creator in righteousness, men and women need something more than an awareness of His existence through general revelation. We also need to know who and what He is, where He can be found, and how He may be approached; He reveals this in His Word. Brian A. Russell here guides us through what the Bible says about the attributes of God.s